Industrial Engineering and Ergonomics Visions, Concepts, Methods and Tools Festschrift in Honor of Professor Holger Luczak - Schlick, Christopher M. (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Human work is one of the main forces driving the development of our society, economy and quality of life. Statistics from the International Labour Organization indicate that there are currently 1.1 billion "economically active individuals" on five continents who on average spend more than half of their waking hours at work. This number entails an enormous potential impact for concepts, methods and tools of industrial engineering and ergonomics in the design of human work. This book focuses on the analysis, design and evaluation of complex work systems and work processes in engineering design, manufacturing and service. Its 46 scientific articles, contributed by internationally recognized researchers from 12 countries, provide unique insights into the latest developments and trends in these areas. The book is clearly organized and distinguishes seven levels of abstraction that emerge when human work is studied using different analytical approaches and different time scales.